Soundtrack as Discourse: Irony, Nostalgia, and Meaning in “Bye Bye Bye” - Palangan, Barans Irawan; Telenta, Pratama Irwin; Susanto, Allvian I.F.; Febrianto, Aziza Restu (Universitas Stikubank (UNISBANK) Semarang, 2026)
Films often use popular music to guide how viewers understand a story, relying on the audience's emotional connection to familiar hits. This research analyzes the inclusion of *NSYNC’s “Bye Bye Bye” in Deadpool & Wolverine to determine the discursive role of a famous pop track in a modern superhero movie. The study investigates how the intersection of lyrics, film visuals, and cultural history creates new meanings. Specifically, it explores how a well-known song is recontextualized to generate irony and humor while influencing the film’s underlying message. Applying a three-dimensional Critical Discourse Analysis, the study examines the song's linguistic features (micro-level), its production and marketing within the franchise (meso-level), and its relationship to broader social norms (macro-level). The results indicate that the song’s repetitive and accessible nature makes it a flexible tool for cinematic reinterpretation. Ultimately, the analysis reveals that while the use of the song seems subversive, it tends to uphold existing cultural values rather than challenge them. The study highlights how soundtracks utilize familiarity to build meaning, demonstrating the effectiveness of multi-layered discourse analysis in studying pop culture. Keywords: Critical Discourse Analysis, Deadpool &Wolverine, Film Soundtracks, Recontextualization, Popular Music